Immobilization of specific proteins to titanium surface using self-assembled monolayer technique. Issue 10 (October 2015) - Tack, L.; Schickle, K.; Böke, F.; Fischer, H.
Abstract Objectives The bone bonding to a titanium dental implant surface strongly depends on their individual chemical surface properties. Here we hypothesize that a tailored surface chemistry obtained through a self-assembled monolayer technique on the titanium surface and subsequent immobilization of biological agents can be arbitrarily adjusted to meet any desired requirements for future dental applications. Methods Self-assembled monolayers were applied to titanium surfaces inducing –(CH2)nCH2, –(CH2)n–NH2, –(CH2)n–OH, and –(CH2)n–COOH functional groups. To investigate the cytocompatibility of these modifications, human mesenchymal stem cells (MSCs) were seeded on the functionalized surfaces and characterized by live/dead staining and cell proliferation. Additionally, bovine serum albumin (BSA) as a model protein was immobilized on the functionalized surfaces. Results Water contact angle measurements and X-ray photoelectron spectroscopy (XPS) proved a successful functional group coupling on the surface. Cell proliferation and viability was supported on the functionalized surfaces. The immobilized proteins were detected on each functionalized surface with an increase in quantity in the following order: –(CH2)n–COOH< –(CH2)n–NH2, –(CH2)n–OH< –(CH2)nCH2. The successful immobilization of BSA by carboxyl-to-amine cross-linking was spectrophotometrically confirmed. Significance It was proved that self-assembled monolayer (SAM)-technique can be utilized to couple diverse functional groups and biological agents on titanium surfaces allowing controlled design of their surface chemistry. The novel functionalization technique and the new knowledge on MSCs response holds great potential for the development of novel functionalized and biologically activated titanium-based dental implants.